Les faux-amis dans les notices lexicales des dictionnaires bilingues au service de l’apprentissage du FLE - Witold Ucherek; Monika Grabowska (Romanica Wratislaviensia)
The article is devoted to lexical notes concerning false friends found in two compact Polish-French and French-Polish general dictionaries that have been commercially available for about fifteen years. In total, 52 text boxes containing these notes, written in Polish, were examined, and their didactic value is undeniable. However, the analysis has shown that when creating this type of note, more attention should be paid to the section of the dictionary in which they should appear, the choice of false friends, as some errors are less likely than others, and the validity of linguistic information.